An Update of Mobile Colistin Resistance in Non-Fermentative Gram-Negative Bacilli - Khuntayaporn, Piyatip; Thirapanmethee, Krit; Chomnawang, Mullika Traidej (Frontiers in Cellular and Infection Microbiology, 2022)
Colistin, the last resort for multidrug and extensively drug-resistant bacterial infection treatment, was reintroduced after being avoided in clinical settings from the 1970s to the 1990s because of its high toxicity. Colistin is considered a crucial treatment option for Acinetobacter baumannii and Pseudomonas aeruginosa, which are listed as critical priority pathogens for new antibiotics by the World Health Organization. The resistance mechanisms of colistin are considered to be chromosomally encoded, and no horizontal transfer has been reported. Nevertheless, in November 2015, a transmissible resistance mechanism of colistin, called mobile colistin resistance (MCR), was discovered. Up to ten families with MCR and more than 100 variants of Gram-negative bacteria have been reported worldwide. Even though few have been reported from Acinetobacter spp. and Pseudomonas spp., it is important to closely monitor the epidemiology of mcr genes in these pathogens. Therefore, this review focuses on the most recent update on colistin resistance and the epidemiology of mcr genes among non-fermentative Gram-negative bacilli, especially Acinetobacter spp. and P. aeruginosa.